Comparative Analysis of the State of Greening Energy Systems in the EEU: Opportunities for Energy Transition - Vahe S. Davtyan; Silva R. Khachikyan (RUDN Journal of Economics)
The study provides a comparative analysis of the state of greening energy systems in the Eurasian Economic Union (EEU) member countries. The international climate regime, the main stages and problems of its implementation are presented. Through an analysis of scientific literature, it is determined that, despite the traditional “brown” trend in energy development in the EEU member states, nevertheless, they are experiencing an increasing demand for a “green transition”, caused by objective challenges of sustainable development. The prospects for the development of low-carbon energy in the EEU are assessed, and therefore the role of nuclear energy and renewable energy sources in the implementation of the “energy transition” strategy is highlighted. Particular attention is paid to the analysis of the main legislative acts, strategic documents and national concepts of the EAEU member countries in the field of low-carbon development of energy systems. A comparative analysis of nationally determined contributions (NDC) for achieving the goals of the Paris Agreement, as well as carbon dioxide emissions into the atmosphere in the EEU member states is carried out. These indicators are analyzed in the context of the structure of national economies. The structures of electricity production by generating capacity are separately considered, which made it possible to determine the potential for the implementation of the energy transition in an intercountry context. It is established that in order to achieve the set goals for greening energy systems in the EEU, it is necessary to develop uniform standards for regulating the energy industry, especially in matters of ensuring energy efficiency.